If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -1x = 11 Solving -2 + -1x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 11 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 11 + 2 -1x = 11 + 2 Combine like terms: 11 + 2 = 13 -1x = 13 Divide each side by '-1'. x = -13 Simplifying x = -13
| x-12/3=-21 | | 6a-2+7=-1 | | 5x=-7x+6x | | 4(x+4)=6(x+6) | | 4x-7=-40+7x | | -8-k=20 | | 4b+1+5=-10 | | 9-2c=55 | | 18.08+6.00p=72.48 | | 14y=-7x+21 | | X/3-6=2 | | -9+7x=6x-2 | | 5x^2+5y^2-25x+35y-85=0 | | (x+2)5=50 | | 7=x/2-14 | | (50x^2)-20x=0 | | (6x^2)(-3x^5)= | | 1/5x=1/3x-2 | | 4(2m-5)=6m-70 | | x+2(5)=50 | | cos^2x-2sinx-2=0 | | 6i(5-2i)= | | 7x+2=12+6x | | 0=81x^2+25 | | 8x=6x-90 | | x+120=2x+120 | | 13=13+5x | | 5/9x5/5= | | 5x+2+-x=-4x | | -36+7n=-6(1-2n) | | 2p-2+p= | | X^3+x^2+6x+6=0 |